Economic cooperation among OIC countries: a case study of Turkey and Malaysia - Kayadibi, Saim (Faculty of Business Management, UiTM, 2015)
This paper investigates the bilateral relationship between two Organization of Islamic Cooperation (OIC) member countries – Turkey and Malaysia – in terms of economic cooperation. Although their cultural, political, and social relationship goes back to the thirteenth century, their current economic relationship has not yet reached the desired level. Although it has grown steadily over the last decade, the annual turnover is not as much as it should be. In 2000 the volume of trade between them was a modest USD 242 million; by 2006 it increased to USD 994 million, which made Malaysia Turkey‟s seventh largest trading partner in Asia. The following year, the trade volume exceeded USD 1.3 billion, an increase of 34 percent. Despite this growing trade, the trade balance has long been in Malaysia‟s favour. Turkey‟s trade deficit amounted to USD 1.2 billion dollars, an increase of 33%, in comparison with the corresponding figures for 2009. Surprisingly, by 2010 Turkish exports to Malaysia had risen to USD 93 million and imports from Malaysia had doubled to more than USD 498 million. Expectations are that bilateral trade in 2012 will rise to USD 2.5 billion, with Malaysian exports making up a large portion of that figure. Since it reached to this expectation it would be USD 5 billion by 2015. As Turkey and Malaysia belong to the OIC, they need to develop a bilateral strategic partnership. For this reason, Ankara has introduced such initiatives as “A Strategy to Improve Commercial and Economic Relations with Asia Pacific Countries,” “The Turkish and Malaysian Joint Economic Commission (JEC),” The Turkish-Malaysian Business Council,” and others. This research will try to find ways to increase their bilateral economic cooperation.